ANALISIS IMPLEMENTASI KEBIJAKAN PEMINDAHBUKUAN DANA PAJAK SECARA ELEKTRONIK DALAM UPAYA MENINGKTAKAN DIGITALISASI LAYANAN PADA KANTOR PELAYANAN PAJAK PRATAMA BEKASI UTARA - Rejeki, Triana Sri; Syadat, Fahrul Anwar (Jurnal Ilmu Administrasi Publik, 2025)
In the introduction of tax digitalization, this became an integral element in implementing the tax reform program initiated by the Directorate General of Taxes (DJP). Currently the Directorate General of Taxes is in the middle implementing the digitalization innovations in tax administration through the new core tax systent The aim of this research was to know how to implement the overbooking Policy Electronics in efforts to Increase digitalization of services in the north Bekasi primary tax services office, as well as obstacles and efforts carried out in this policy. This research uses the method descriptive qualitative research. Data collection from this research involves interviews, observation, and documentation. Theory used in this research is Implementation according to George Edward III (2022). The results of this research indicate that implementation of the electronic book transfer policy in an effort to improve digitalization of services at the North Bekasi Pratama Tax Service Office has not run optimally, if seen from the number of taxpayers in 2023 using e-pbk. This policy is less than optimal caused by several obstacles such as lack of socialization towards taxpayers Efforts that can be made by KPP Pratama North Bekasi are conducting outreach using several methods, adding partners such as Tax Volunteers, and implementing collaboration with third parties